Contextualizing the Malaysian citizenship - Mohamed, Shafizan (Global Academic Ecellence, 2017)
his paper focuses on explicating the unique characteristics of Malaysian politics and citizenship. This is achieved through a short historical background and a general overview of the different issues that build and contest the citizenship experience. Various theoretical positions and debates on the Malaysian citizenship is considered. Also scrutinized is the emergence of New Politics in Malaysia, where political participation shifts from its strict institutional and electoral origins to a more inclusive and contextualized understanding citizen participation. This development in citizenship theory speaks to the ways Malaysians are experiencing a gradual political transformation through the re-invigoration of civil society.